Sociodemographic Characteristics and Learning Styles on Academic Performance in Science - John Paul Badua LPT; Ma. Elizabeth C. Leoveras Ph. D; Elmer D. Dela Rosa Ph. D; Eden S. David Ph. D (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2021)
Learning styles refer to how students process, inculcate, and understand information. In both the traditional face-to-face classes and in the new learning modalities, instances that the students’ learning styles have been overlooked are inevitable that may result in their poor academic performance. Challenge was left on teachers in the utilization of appropriate teaching strategies for the students to maximize the functions of their learning styles. Using the descriptive correlational and comparative design, this study was conducted to examine the relationship of selected sociodemographic characteristics and the dominant learning styles of 385 junior high school students from a city in Nueva Ecija, Philippines to their academic performance. Results revealed that the online learning, absence of assistance when answering written works, absence of tutor, number of siblings, place of residence, academic awards in Grade 6, average hours of review, parents’ educational background, and monthly family income could make students performed better in science under the new normal education. Moreover, ANCOVA revealed that the students’ dominant learning styles have no significant relationship on their academic performance in science. The study concluded that some sociodemographic characteristics may have either positive or negative effect on students’ academic performance but have found out that the dominant learning styles have no known influence.